Detection of Reductase and Catalasse Enzymes in Goats Milk (Capra aegaggrus hircus) Sold in Banda Aceh - Novita, Andi; Putri, Aulia Nuddi Yanti; Herialfian, Herialfian; Isa, M; TR, T Armansyah; Hasan, M (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
This study aims to determine of reductase and catalase enzymes in pasteurized goat's milk sold in Banda Aceh. The sample used was pasteurized goat's milk which was sold in Banda Aceh as many as 30 samples were taken by census. The research method used is a survey study method with a cross-sectional approach. Sample testing using reductase test and catalase test. The results showed that the reductase time of 30 samples of pasteurized goat's milk averaged 3-5 hours and the catalase number of 30 samples of pasteurized goat's milk was below 3 ml. Based on the results, it shows that there are reductase enzymes and catalase enzymes in goat's milk and have good quality in Banda Aceh.